Expectativa de autoeficácia para seguir prescrição de antirretroviral em adultos vivendo com HIV - Ramos Junior, Angelo (2020)
The effectiveness of highly active antiretroviral therapy (HAART) for the human immunodeficiency virus (HIV) is already well established in the scientific literature, however, its effectiveness depends especially on patients' adherence to therapy, which is influenced by several factors. Thus, the expectation of self-efficacy in adhering to HAART should be considered. The aim of this study was to assess whether the expectation of self-efficacy is associated with adherence to HAART. Cross-sectional study developed in an outpatient service to assist infectious diseases linked to a university hospital located in the interior of Rio Grande do Sul, Brazil. The sample consisted of 156 adult participants infected by the virus and who had been followed up at the service for at least three months. Data were collected from the adult characterization questionnaire. To assess self-efficacy, a Self-efficacy scale for Adherence to Antiretroviral Treatment (EEASP) and an adherence rating scale (CEAT-HIV). For data analysis, logistic regression was performed in SPSS 21.0. According to the results of this study, with the exception of item 17, the other items in situation A showed a significant correlation with global adherence. The correlations were weak and the items that had the highest correlation were If I'm healthy (E5) and If I have to take medication several times a day (E13). Items If I'm healthy (E1), If the virus in my blood is so little that it does not appear in the viral load test (E2) and If I'm feeling sick (E8) of situation B showed a significant correlation with global adherence, with item E2 having the greatest correlation, but with a weak magnitude. Items If I'm bored and feeling down (E3), If I am discriminated against or rejected (E4), If I’m with someone I don’t want them to know I have the AIDS virus (E9), If I have to take too many pills (E10), If I'm nervous or irritated (E11) and If the drugs are having a bad effect (E21) of situation C showed a significant correlation, albeit with a weak magnitude, with global adherence. Of these, item E3 showed a greater correlation. It is expected that the results of this study will contribute to the nurses' care practice in teaching, research and extension, expanding the critical and reflective look at the treatment and, mainly, that it be a tool to stimulate self-efficacy in the way of care.